Laser-assisted XUV few-photon double ionization of helium: Joint angular distributions - Liu, Aihua; Thumm, Uwe (My University, 2014)
We investigate few-photon extreme ultraviolet (XUV) double ionization of helium atoms without and in the presence of an assisting infrared (IR) laser field by numerically solving the time-dependent Schrödinger equation in full dimensionality within a finite-element discrete-variable-representation scheme. We discuss joint energy distributions for coplanar emission where the emitted electron momenta and polarization axis of the linearly polarized XUV and IR pulses lie in a plane. Our analysis focuses on joint angular distributions for highly correlated equal-energy-sharing double ionization by absorption of one, two, or three XUV photons and IR-laser-assisted single-photon XUV double ionization.